From Detached Concern to Empathy : Humanizing Medical Practice. (Oxford University Press, USA, 2001)
Physicians recognize the importance of patients' emotions in healing yet believe their own emotional responses represent lapses in objectivity. Patients complain that physicians are too detached. Halpern argues that by empathizing with patients, rather than detaching, physicians can best help them. Yet there is no consistent view of what, precisely, clinical empathy involves. This book challenges the traditional assumption that empathy is either purely intellectual or an expression of sympathy. Sympathy, according to many physicians, involves over-identifying with patients, threatening objectivity and respect for patient autonomy. How can doctors use empathy in diagnosing and treating patients rithout jeopardizing objectivity or projecting their values onto patients? Jodi Halpern, a psychiatrist, medical ethicist and philosopher, develops a groundbreaking account of emotional reasoning as the core of clinical empathy. She argues that empathy cannot be based on detached reasoning because it involves emotional skills, including associating with another person's images and spontaneously following another's mood shifts. Yet she argues that these emotional links need not lead to over-identifying with patients or other lapses in rationality but rather can inform medical judgement in ways that detached reasoning cannot. For reflective physicians and discerning patients, this book provides a road map for cultivating empathy in medical practice. For a more general audience, it addresses a basic human question: how can one person's emotions lead to an understanding of how another person is feeling?